2021
DOI: 10.3390/foods10091981
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Syringe Flow Measurements and Viscosity of Nectar-Thick Beverages for Dysphagia Management

Abstract: Commercial cold beverages thickened with a xanthan gum (XG)-based food thickener were examined at different thickness levels by using the simple, cost-effective syringe flow test (SFT) developed by the International Dysphagia Diet Standardization Initiative (IDDSI). We prepared cold thickened beverage (CTB) samples with different thickener concentrations and measured them by extrapolating the viscosity range (51–350 mPa·s) for nectar-like consistency. CTBs were also measured via the line-spread test (LST), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…On the other hand, the syringe tip with a small diameter used in SFT could be partially or entirely obstructed by particulates formed by the complex interaction between different components of thickeners and beverages (Table 2), potentially impeding the flow of thickened beverages in the syringe (Hadde et al, 2015;Weston and Clarke, 2020). Additionally, the high friction resulting from the direct contact between the syringe surface and the thickened beverage might hinder the outflow of the thickened beverage contained in the syringe (An et al, 2023). These effects of particulates and friction might explain why the SFT value stabilized faster than the LST value at level 3, despite the opposite result observed at level 2 (Table 3).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…On the other hand, the syringe tip with a small diameter used in SFT could be partially or entirely obstructed by particulates formed by the complex interaction between different components of thickeners and beverages (Table 2), potentially impeding the flow of thickened beverages in the syringe (Hadde et al, 2015;Weston and Clarke, 2020). Additionally, the high friction resulting from the direct contact between the syringe surface and the thickened beverage might hinder the outflow of the thickened beverage contained in the syringe (An et al, 2023). These effects of particulates and friction might explain why the SFT value stabilized faster than the LST value at level 3, despite the opposite result observed at level 2 (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have also reported a strong exponential relationship between the LST values of thickened beverages and the rheological properties relevant to fluid viscosity ( Nicosia and Robbins, 2007 ; Kim et al, 2014b ; Kim et al, 2018 ). One common approach to compare the thickness of thickened fluids involves measuring the average flow distance in the quadrant directions of thickened fluid poured into a cylindrical container ( Mann and Wong, 1996 ; Nicosia and Robbins, 2007 ; Barbon and Steele, 2018; Kim et al, 2018 ; Giura et al, 2021; Jeong et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…During the eating process, foods with lower viscosity are more likely to cause penetration and aspiration ( Newman et al, 2016 ). As a result, caregivers often thicken the food of the dysphagia patients ( Watanabe et al, 2018 ), but the thickened food can make it more difficult for the patient to transport it through the mouth ( Jeong et al, 2021 ), which can cause the food to stay in their mouth longer. For patients with oral transit difficulties and delayed swallowing initiation, the longer the food stays in the oral cavity, the higher the degree of hydrolysis by salivary amylase even if the food is thickened ( Abu-Hasan et al, 2014 ; Sole et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%